The ABORTED MICROSPORES Regulatory Network Is Required for Postmeiotic Male Reproductive Development in Arabidopsis thaliana([W])([OA]) - Xu, Jie (American Society of Plant Biologists, 2010)
The Arabidopsis thaliana ABORTED MICROSPORES (AMS) gene encodes a basic helix-loop-helix (bHLH) transcription factor that is required for tapetal cell development and postmeiotic microspore formation. However, the regulatory role of AMS in anther and pollen development has not been fully defined. Here, we show by microarray analysis that the expression of 549 anther-expressed genes was altered in ams buds and that these genes are associated with tapetal function and pollen wall formation. We demonstrate that AMS has the ability to bind in vitro to DNA containing a 6-bp consensus motif, CANNTG. Moreover, 13 genes involved in transportation of lipids, oligopeptides, and ions, fatty acid synthesis and metabolism, flavonol accumulation, substrate oxidation, methyl-modification, and pectin dynamics were identified as direct targets of AMS by chromatin immunoprecipitation. The functional importance of the AMS regulatory pathway was further demonstrated by analysis of an insertional mutant of one of these downstream AMS targets, an ABC transporter, White-Brown Complex homolog, which fails to undergo pollen development and is male sterile. Yeast two-hybrid screens and pull-down assays revealed that AMS has the ability to interact with two bHLH proteins (AtbHLH089 and AtbHLH091) and the ATA20 protein. These results provide insight into the regulatory role of the AMS network during anther development.